Urban to rural COVID‐19 progression in India: The role of massive migration and the challenge to India's traditional labour force policies. (14th September 2021) - Sahoo, Prafulla Kumar; Biswal, Suchismita; Kumar, Hemant; Powell, Mike
Abstract: The coronavirus disease‑2019 (COVID‐19) has emerged as a deadliest disease in the 21st century. Initially in India, this disease was concentrated in major urban cities like Mumbai, Delhi, Gujarat, and Chennai, which were the national hotspots for the COVID‐19 pandemic. However, in subsequent months, returning migrants (mainly day labour) brought the disease back to their home; this vector triggered significant spread to semi‐urban and rural areas. This highlighted serious concerns in rural India, where access to sophisticated healthcare and mitigation strategies were lacking. There is little data on this new pattern of disease spread. This article provides a short review for tracking the spread of COVID‐19 into major rural states in India based on understanding urban‐rural workforce migration relative to the growing proportion of the nation's COVID‐19 caseload between May‐September 2020.